2020
DOI: 10.3390/ma13163514
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Air-Entraining Behavior Based on the Interactions between Cement Particles and Selected Cationic, Anionic and Nonionic Surfactants

Abstract: The essential role of the air void size distribution in air-entrained cementitious materials is widely accepted. However, how the air-entraining behavior is affected by features such as the molecular structure of air-entraining agents (AEAs), the type of solid particles, or the chemical environment of the pore solution in fresh mortars is still not well understood. Besides, methods to assess the interaction between AEAs and cement particles are limited. Thus, in this study, the air-entraining behaviors of thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 83 publications
(96 reference statements)
0
17
0
Order By: Relevance
“…The main parameters providing foam stability are surface tension and the Gibbs' effect of the surface elasticity of thin liquid films which are reflected in the stability of separate bubbles [40,41]. Surface active substances (surfactants), while being added to the water phase, reduce surface tension at the gas-liquid boundary and decrease energy loss which results in the stabilization of the foam structure.…”
Section: The Main Physical-chemical Properties Of Liquid-gas Foamsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main parameters providing foam stability are surface tension and the Gibbs' effect of the surface elasticity of thin liquid films which are reflected in the stability of separate bubbles [40,41]. Surface active substances (surfactants), while being added to the water phase, reduce surface tension at the gas-liquid boundary and decrease energy loss which results in the stabilization of the foam structure.…”
Section: The Main Physical-chemical Properties Of Liquid-gas Foamsmentioning
confidence: 99%
“…The heterophase system (water droplets in air phase) of Earth's atmosphere has been well studied, supramolecular forces acting at the boundaries of phases, conditions affecting the size and stability of droplets etc. have been extensively analyzed [39,40,45]. It is reasonable to assume that the laws behind intermolecular relations, the forces of intermolecular attraction and equilibrium distances between the surface layer molecules in liquid-gas systems on Venus are analogous to those on Earth.…”
Section: The Basic Mechanisms Of Foam Formation In Earth Ecosystemsmentioning
confidence: 99%
See 1 more Smart Citation
“… Petit et al showed that, to maintain high foam stability, it is necessary to obtain monolayer adsorption of the surfactant on the solid’s surface [ 26 ]. Liu et al studied the air void parameters of mortars and the adsorption of different types of surfactants on cement grains [ 27 ]. The presented explanation was contrary to the aforementioned results obtained by Planck and Zingg [ 8 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al studied the air void parameters of mortars and the adsorption of different types of surfactants on cement grains [ 27 ]. The presented explanation was contrary to the aforementioned results obtained by Planck and Zingg [ 8 , 19 ].…”
Section: Introductionmentioning
confidence: 99%